PAI Digital Mosaic: Learning Creation Through Software-Based Media - Ratna Putri Pradita; Qo-Idah Ariq Pangesti; Anugrah Ainul Yakin; Muh. Alif Kurniawan (Kasyafa: Jurnal Pendidikan Agama Islam, 2024)
In the increasingly developing digital era, Islamic Religious Education (PAI) learning faces new challenges and opportunities. This article introduces the concept of "Digital Mosaic PAI," an innovative approach that integrates software-based media in the learning process. By utilizing a variety of interactive applications and multimedia platforms, the authors explore creative ways to increase student participation and understanding. This research identifies various types of effective digital media, analyzes implementation in the classroom, and their impact on understanding and applying religious values. As a result, PAI learning has not only become more dynamic, but is also able to hone students' critical skills and creativity. This article is expected to be a source of inspiration for educators to create more meaningful and impactful learning experiences.